THE INFLUENCE OF THE CIRCULAR ECONOMY ON ECONOMIC GROWTH: LITERATURE REVIEW - Safariyani, Eva; Taufiqurahman, Endang (STIE PGRI Dewantara Jombang, 2023)
The objectives of this study, based on the framework of realizing the circular economy model, are: a) Knowing the environmental factors that influence the circular economy and b) Knowing the circular economy variables that affect economic growth. This study uses the method of literature analysis from various research literature that has been done. The data used is secondary data: books and international journals. The results of the study can conclude two things. First, the circular economy affects economic growth through a) The importance of development from an environmental sustainability perspective, b) Business innovation that takes into account environmental aspects, c) Recycling economic activities that do not reduce environmental quality, d) the importance of investing in recycling infrastructure and natural resources innovative. Second, the factors that influence the circular economy are a) Human Capital, b) Development with an environmental sustainability perspective, c) Maintaining the value of resources, d) Socio-ecological and anthropological factors, e) Business innovation, f) Innovation of social progress, h) Redesign of processes and cycles of materials, h) Need for public attention, i) Need to promote 3R on circular consumption, j) Goods/services management system, k) Invest in recycling infrastructure.